Bridging gaps in Bangladesh’s rice seed system - Habib, Muhammad Ashraful; Hossain, Sk Mosharraf; Nayak, Swati; Islam, Saidul; Nuruzzaman (International Rice Research Institute, 2025)
Rice remains central to Bangladesh’s agriculture and food security, yet inefficiencies in seed demand forecasting and distribution continue to limit the timely availability and adoption of quality, climate-resilient rice varieties. To address these challenges, the International Rice Research Institute (IRRI), in partnership with the Bangladesh Agricultural Development Corporation (BADC) and the PARTNER Project, organized a series of regional workshops titled “Seed System Gap Analysis—Insight to Implementation” across major rice-growing regions of Bangladesh. Engaging over 130 stakeholders from the public and private sectors, the workshops applied participatory analytical tools to identify bottlenecks in seed forecasting, varietal replacement, seed mobility, and quality assurance. Insights generated are guiding the enhancement of SeedCast, a digital, demand-driven seed forecasting platform, and informing policy recommendations to strengthen Bangladesh’s seed system. The initiative underscores the importance of inclusive, technology-enabled, and evidence-based approaches to improve seed system efficiency, reduce wastage, and enhance farmer access to quality seeds nationwide.